Studi Kenyamanan dan Ketersediaan Pelayanan Ruang Keberangkatan Terminal Bandar Udara Haji Hasa Aroeboesman Ende - Jhon Alfred Alfred D.D; DVX. Deddy Kurniawan (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2023)
Ende City as the capital of Ende Regency which has the potential to become a center of economic growth, has transportation facilities and infrastructure that support one of which is adequate air routes. Haji Hasan Aroeboesman Airport connects Ende City with several cities in East Nusa Tenggara Province and other cities in Indonesia such as Denpasar, Makassar and Surabaya. Haji Hasan Aroeboesman Airport annually experiences an increase in the number of passengers. Based on data from the Central Statistics Agency, the flow of passengers with total departures and arrivals in 2018 reached 213,590 passengers. The number of aircraft is 2451 aircraft, luggage is 857,741 kg, and goods are 98,208 kg. With this increase, this will have an impact on the capacity and facility needs in the airport terminal. Airports are also required to be able to accommodate changes in activities and developments that may occur in the future. This study aims to conduct studies related to theavailability of Haji Hasan Aroeboesman Airport services so that it can provide recommendations for efforts to improve the service capabilities of Haji Hasan Aroeboesman Airport.  The method used in this study uses a deductive method, where the data obtained are compared and then taken positive and useful things and consider the aspects of the shortcomings. The results of the study on the comfort and availability of departure room services at Haji Hasan Aroeboesman Airport in general are the need for a redesign to overcome various problems such as an increase in the number of passengers, aircraft and goods from year to year.  And specifically, various problems were found such as: the standard for space needs does not meet the LOS (Level of Service) standards set by IATA, does not have an area specifically for commercial areas and other supporting facilities, and the level of comfort felt by users (repondents) is only 26%.